Evaluation of Diaphragmatic Electromyograms in Radiofrequency Ablation of Atrial Fibrillation: Prospective Study Comparing Different Monitoring Techniques. (28th November 2014) - MIYAZAKI, SHINSUKE; ICHIHARA, NOBORU; TANIGUCHI, HIROSHI; HACHIYA, HITOSHI; NAKAMURA, HIROAKI; USUI, EISUKE; KANAJI, YOSHIHISA; TAKAGI, TAKAMITSU; IWASAWA, JIN; KUROI, AKIO; HIRAO, KENZO; IESAKA, YOSHITO
Diaphragmatic Electromyograms During AF Ablation Background The utility of compound motor action potential (CMAP) monitoring for anticipating phrenic nerve injury (PNI) during cryoballoon ablation has been reported. We sought to compare two different CMAP recording techniques and evaluated the feasibility during pulmonary vein antrum isolation (PVAI) and superior vena cava isolation (SVCI) using radiofrequency energy. Methods and Results Forty‐two patients undergoing paroxysmal atrial fibrillation ablation were prospectively enrolled. SVCI was performed following PVAI if SVC potentials were observed. CMAPs were recorded 3 times (before and after PVAI, and after SVCI) simultaneously from surface electrodes (CMAPsuf) and a decapolar catheter in the subdiaphragmatic hepatic vein (CMAPabd). The baseline CMAPsuf and CMAPabd were 0.92 ± 0.36 and 0.65 ± 0.43 mV except in one case with catheter inaccessibility. The CMAPsuf did not correlate with the body mass index, or CMAPabd. In 2 and 9 patients, the CMAPsuf and CMAPabd amplitudes were < 0.5 and < 0.3 mV, respectively. The diaphragm to catheter distance was significantly longer in cases with a CMAPabd < 0.3 mV than one > 0.3 mV (39.2 ± 10.8 vs. 21.5 ± 6.6 mm, P < 0.0001). Two cases with a CMAPsuf < 0.5 mV had larger amplitudes on the CMAPabd. In 1 patient, apparent PNI occurred during the SVCI, and the CMAP disappeared after the SVCI in both techniques. The CMAPs did not significantly decrease after the PVAI and SVCI; however, a >30% decrease was observed in 2 patients in both techniques. In both, no PNI was apparent on fluoroscopy or chest X‐ray. Conclusions Stable evaluable CMAPs were obtained with the CMAPsuf in most patients. Monitoring with the CMAPabd could be an alternative and complementary method.